2014
DOI: 10.1080/14999013.2014.906519
|View full text |Cite
|
Sign up to set email alerts
|

Historical-Clinical-Risk Management-20, Version 3 (HCR-20V3): Development and Overview

Abstract: The HCR-20 Version 3 (HCR-20 V3 ) was published in 2013, after several years of development and revision work. It replaces Version 2, published in 1997, on which there have been more than 200 disseminations based on more than 33,000 cases across 25 countries. This article explains (1) why a revision was necessary, (2) the steps we took in the revision process, (3) key changes between Version 2 and Version 3, and (4) an overview of HCR-20 V3 's risk factors and administration steps. Recommendations for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
204
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(217 citation statements)
references
References 21 publications
1
204
0
12
Order By: Relevance
“…In response to the limitations of both actuarial and unstructured clinical judgment methods of risk assessment, the structured professional judgment model emerged. This approach combines the strengths of both approaches by using both statistical prediction and clinician interpretation and is gradually replacing unstructured approaches to risk assessment in BIPs (Douglas & Reeves, 2010). Structured judgment methods use actuarial approaches to yield a measure of predictive accuracy for violent outcomes (Heilbrun, Yasuhara, & Shah, 2010), but ultimately, the clinician has the power to interpret the information and to make practical decisions.…”
Section: Assessment Protocol and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the limitations of both actuarial and unstructured clinical judgment methods of risk assessment, the structured professional judgment model emerged. This approach combines the strengths of both approaches by using both statistical prediction and clinician interpretation and is gradually replacing unstructured approaches to risk assessment in BIPs (Douglas & Reeves, 2010). Structured judgment methods use actuarial approaches to yield a measure of predictive accuracy for violent outcomes (Heilbrun, Yasuhara, & Shah, 2010), but ultimately, the clinician has the power to interpret the information and to make practical decisions.…”
Section: Assessment Protocol and Instrumentsmentioning
confidence: 99%
“…The first is unstructured clinical judgment, which is the most commonly used approach by clinicians (Douglas & Reeves, 2010), and in this approach, the clinician's professional opinion, intuition, and experience are used for gathering information and deciding what information is most related to future violence risk. Because these approaches do not yield a measurable metric of risk, they are impossible to empirically assess (Nicholls et al, 2013).…”
Section: Assessment Protocol and Instrumentsmentioning
confidence: 99%
“…The most widely used SPJ tool in forensic psychiatry settings in the UK is the Historical Clinical Risk Management-20 (HCR-20), which is currently in its third version (HCR-20 V3 ) 3. Both retrospective and prospective research has suggested that the HCR-20 is predictive of future violence, across a range of settings 3–5.…”
Section: What Is Already Known About This Topicmentioning
confidence: 99%
“…Although the HCR-20 has been repeatedly associated with moderate to good predictive power,3 this is largely based on assessments completed for research. In clinical settings, completion of an accurate and thorough HCR-20 is time-consuming (up to 14 hours on average) 14.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…One study followed up reoffending at 1, 2 and 5 years post-discharge, 35 whereas another set of studies using the same data-set reported on whether there was reoffending behaviour within the 2 years following discharge from hospital. 78,79 Another, based in Australia, considered arrest data and 'any criminal justice involvement' following discharge. 80 A series of studies, based in the community, considered whether treatment within the context of a community-based forensic service led to a reduction in offending behaviours.…”
Section: Effectivenessmentioning
confidence: 99%